2009
DOI: 10.1186/1471-2229-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparative analysis of HMW glutenin 1Ay alleles with differential expressions

Abstract: Background: High-molecular-weight glutenin subunits (HMW-GSs) have been considered as most important seed storage proteins for wheat flour quality. 1Ay subunits are of great interest because they are always silent in common wheat. The presence of expressed 1Ay subunits in diploid and tetraploid wheat genotypes makes it possible to investigate molecular information of active 1Ay genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 49 publications
3
56
0
Order By: Relevance
“…The subunits Glu-A1y1 and Glu-A1y2 observed in this study were similar to the subunits observed by Hu et al (2011) in three species of Triticum monococcum L., Triticum boeticum Boiss and Triticum urartu Tum, while the subunit Glu-A1y3 was characterized as the study of diploid accessions of Triticum aegilopoides by Jiang et al (2009).…”
Section: Discussionsupporting
confidence: 88%
“…The subunits Glu-A1y1 and Glu-A1y2 observed in this study were similar to the subunits observed by Hu et al (2011) in three species of Triticum monococcum L., Triticum boeticum Boiss and Triticum urartu Tum, while the subunit Glu-A1y3 was characterized as the study of diploid accessions of Triticum aegilopoides by Jiang et al (2009).…”
Section: Discussionsupporting
confidence: 88%
“…dicoccoides, which is the oldest species of emmer wheat with the genome AABB (Feldman et al 1995;Chantret et al 2005). The 1Ay subunit JF519636 was similar to that of AY245578 from T. urartu line IZ29-1, but differed from the other nine 1Ay genes in electrophoretic mobility in SDS-PAGE (Wan et al 2002;Bai et al 2004;Jiang et al 2009;Hu et al 2010). However, its predicted protein secondary structure was different from that of AY245578 in the relative content and number of motifs because of 25 different amino acids (Figure 3, Tables 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…In common wheat, the gene coding the subunit 1Ay is unexpressed because of a premature stop codon (Forde et al 1985) or the insertion of a transposon-like element within its coding region (Harberd et al 1987). However, this subunit is active in many lines of diploid wheat (AA) and the tetraploid wheats T. turgidum (AABB) and T. timopheevii (AAGG) (Ciaffi et al 1991(Ciaffi et al , 1998Ma et al 2007;Jiang et al 2009;Xu et al 2009;Hu et al 2012). Active 1Ay genes have been cloned from the wild diploid wheats T. urartu and T. monococcum ssp.…”
mentioning
confidence: 99%
“…aegilopoides, and T. monococcum ssp. monococcum (Jiang et al 2009;Hu et al 2010;Gutiérrez et al 2011;Hu et al 2012). In this study, 1Ay subunit is expressed in 7 accessions of T. monococcum ssp.…”
Section: Discussionmentioning
confidence: 99%